Search for Nodulation and Nodule Development-related cystatin genes in the genome of Soybean (Glycine max) - Songli Yuan; Rong Li; Lei Wang; Haifeng Chen; Chanjuan Zhang; Limiao Chen; Qingnan Hao; Zhihui Shan; Xiaojuan Zhang; Shuilian Chen; Zhonglu Yang; Diezhen Qiu; et al. (Frontiers in Plant Science, 2016)
Nodulation, nodule development and senescence directly affects nitrogen fixation efficiency, and previous studies have shown that inhibition of some cysteine proteases delay nodule senescence, so their nature inhibitors, cystatin genes, are very important in nodulation, nodule development and senescence. Although several cystatins are actively transcribed in soybean nodules, their exact roles and functional diversities in legume have not been well explored in genome-wide survey studies. In this report, we performed a genome-wide survey of cystatin family genes to explore their relationship to nodulation and nodule development in soybean and identified 20 cystatin genes that encode peptides with 97~245 amino acid residues, different isoelectric points (pI) and structure characteristics, and various putative plant regulatory elements in 3000 bp putative promoter fragments upstream of the 20 soybean cystatins in response to different abiotic/biotic stresses, hormone signals and symbiosis signals. The expression profiles of these cystatin genes in soybean symbiosis with rhizobium strain Bradyrhizobium japonicum strain 113-2 revealed that 7 cystatin family genes play different roles in nodulation as well as nodule development and senescence. However, these genes were not root nodule symbiosis (RNS) - specific and did not encode special clade cystatin protein with structures related to nodulation and nodule development. Besides, only two of these soybean cystatins were not upregulated in symbiosis after ABA treatment. The functional analysis showed that a candidate gene Glyma.15G227500 (GmCYS16) was likely to play a positive role in soybean nodulation. Besides, evolutionary relationships analysis divided the cystatin genes from Arabidopsis thaliana, Nicotiana tabacum, rice, barley and four legume plants into three groups. Interestingly, Group A cystatins are special in legume plants, but only include one of the above-mentioned 7 cystatin genes related to nodulation and nodule development. Overall, our results provide useful information or clues for our understanding of the functional diversity of legume cystatin family proteins in soybean nodulation and nodule development and for finding nodule-specific cysteine proteases in soybean.